Readers’ acceptance of Ian McEwan novels in Mainland China: a systematic review - Wen Nie; Leng Chan Siaw; Shobihah binti Abang Abay Dayang; Ayuni binti Mokhd Isa Nur (RUDN Journal of Studies in Literature and Journalism)
With the accelerated development of globalisation and the deepening of cultural exchanges, cross-cultural translation and literary reception have become important topics in contemporary literary studies. This review aims to explore readers’ acceptance of Ian McEwan’s novels in mainland China. To this end, the databases of CNKI, EBSCO, Web of Science, Taylor and Francis, and Science Direct have been explored, and twenty-one studies published between 2000 and 2024 have been analysed. A systematic review was used as a research methodology, and the studies were analysed using a content analysis method. The findings revealed that there is rich research on Ian McEwan’s novels but very few significant studies on how ordinary readers accept translated Ian McEwan novels in mainland China. Moreover, other studies have concluded that Chinese readers widely and extensively accept Ian McEwan’s novels as they provoke emotional feelings, arouse ethical considerations, and compel readers to reflect critically. The findings have provided researchers in literature, translation, and intercultural studies with a comprehensive understanding of the current state of reception of Ian McEwan novels in China.